Polybenzimidazole based film forming polymeric ionic liquids: synthesis and effects of cation-anion variation on their physical properties - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Rewar, Anita S.; Kharul, Ulhas K. (Polymer Chemistry, 2014)
Polymeric ionic liquids (PILs) are gaining wide attention due to their tunable properties and applicability in various upcoming areas, including membranes for CO2 separation. The known methodologies yield PILs that are difficult to convert into film form. The present work investigates a synthetic approach for obtaining PILs based on a strong film forming with a fully aromatic rigid backbone while incorporating ionic liquid character in it. Three structurally different polybenzimidazoles (PBI-I, PBI-BuI and ABPBI) were N-quaternized by a methyl group, followed by iodide exchange with various promising anions. The extent of iodide exchange by another anion was high enough (>94% in most cases). Most of the resulting PILs with various anions offer mechanically strong films, with the exception of those based on acetate and benzoate as an anion. Although the base PBI has excellent film forming ability, this result conveyed the role of anion in governing the film forming ability of the PIL. Salient features of this methodology include a fully aromatic polycation backbone, wide structural tunability (by virtue of variation not only of the anion/cation, but also with N-substituent) and introducing two IL characters per repeat unit of a PIL (except for PILs based on ABPBI). Attempted PIL structural variations showed diverse property variations in bulk and surface properties (solvent solubility, contact angle, water sorption, thermal stability, polyelectrolyte behaviour, CO2 sorption and ionic conductivity). Mechanical properties of film forming PILs exhibited high enough tensile strength, conveying their applicability as membrane materials.